Reflective practice during action learning in management development programmes. Issue 2 (3rd August 2020) - Robertson, Jane; Le Sueur, Heidi; Terblanche, Nicky
Abstract : Purpose: This study aims to investigate the aspects that influence reflective practice during an action learning approach to management development programmes (MDPs). Design/methodology/approach: A narrative inquiry approach was used to gather interview and pictorial data from 16 participants who had attended an action learning oriented MDP. Data were translated into interpretive stories using McCormack's lenses, which were further analysed using thematic analysis. Findings: Two key themes emerged: dealing with emotions and practising reflection. Participants initially found reflecting uncomfortable, but showed courage by persevering. Participants had to learn how to reflect and set aside time for it, while valuing support and guidance from their action learning facilitator. Research limitations/implications: The findings and recommendations may not be relevant to all types of action learning as action learning forms and contexts differ. Practical implications: Reflective practice is the responsibility of both the participant and the action learning facilitator. Participants need to create the time and space to learn, be fully present during reflection, practice mindfulness and have the courage to be uncomfortable while reflecting. Action learning facilitators could encourage reflection by creating a safe learning environment, selecting a diverse action learning team, designing reflection time into the MDP and helping participants apply reflection tools. Originality/value: Reflective practice enhances learning; yet there is a need to better understand reflective practice in an action learning context. This study provides empirical evidence of the aspects that influence the reflection process and outcomes as well as practical guidelines to participants and facilitators on how to promote reflection.